Robert Spitzer's legacy: agreement is halfway to truth - Tyrer, Peter (BJPsych Bull, 2018)
Bob Spitzer died in December 2015 but is not likely to be forgotten quickly. His Herculean task in reforming psychiatric diagnosis, mainly by the development of the third edition of the Diagnostic and Statistical Manual of Mental Disorders in 1980, has been acknowledged by many, but it remains unfinished. To complete the process, we need more than good diagnostic reliability, we need better veracity. DECLARATION OF INTEREST: None.